2012
DOI: 10.3928/01484834-20120820-05
|View full text |Cite
|
Sign up to set email alerts
|

Learning Opportunities in Case Studies for Becoming a Reflective Nurse Practitioner

Abstract: The transition from RN to nurse practitioner presents challenges. Because nurse practitioners require deeper critical decision-making abilities to provide safe and quality health care, the Master in Advanced Nursing Practice curriculum implemented reflective case studies to facilitate active and reflective learning. To identify the learning opportunities, we performed a qualitative interpretative study of 77 reflective case studies written by students enrolled in the program. Analysis revealed two categories o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Master‐educated nurses are supposed to possess the reflective and critical thinking abilities needed in more complex care settings (ter Maten‐Speksnijder et al . ). A more reflective attitude on professional performance is desirable, but can make persons more stringent in judging their self‐efficacy (Desmedt , Koole et al .…”
Section: Discussionmentioning
confidence: 97%
“…Master‐educated nurses are supposed to possess the reflective and critical thinking abilities needed in more complex care settings (ter Maten‐Speksnijder et al . ). A more reflective attitude on professional performance is desirable, but can make persons more stringent in judging their self‐efficacy (Desmedt , Koole et al .…”
Section: Discussionmentioning
confidence: 97%
“…In the case studies, the use of reflective practice was diffuse; personal values and behaviors were explored, albeit mostly to motivate activities and not to critically question performances. In an earlier study, we also found that the acquisition of reflective abilities is a complex transitional process for APN students (Ter Maten-Speksnijder et al, 2012). Because the case study method encourages and facilitates this process, the results of this study showed the importance to improve the use of this educational tool in Master programs, especially when organized as a work-study program.…”
Section: Discussionmentioning
confidence: 84%
“…To foster the competence development of nurses and peer workers, the case reports in the present study offer a wealth of relevant practical cases, particularly suitable for this purpose. Previous research in the field of the transition process of nurse practitioners already demonstrated how reflective case vignettes are helpful to deliver compassionate and person-centred care (Ter Maten-Speksnijder et al 2012). The cases collected in the present study could be helpful during discussions among and between nurses and peer workers to determine and define their specific role-related competences and strengthen reflective practice.…”
Section: Relevance For Practicementioning
confidence: 75%
“…Previous research in the field of the transition process of nurse practitioners already demonstrated how reflective case vignettes are helpful to deliver compassionate and person-centred care (Ter Maten-Speksnijder et al 2012). Previous research in the field of the transition process of nurse practitioners already demonstrated how reflective case vignettes are helpful to deliver compassionate and person-centred care (Ter Maten-Speksnijder et al 2012).…”
Section: Relevance For Practicementioning
confidence: 99%